Agia marina and Peristereònas: two new epipalaeolithic sites on the Island of Lemnos (Greece) - Efstratiou, Nikos (2022)
The surveys carried out along the coasts of the island of Lemnos (Greece) have led to the discovery of new Late Epipalaeolithic sites at Agia Marina and Peristereonas. Peristereonas yielded a knapped stone assemblage that is strictly comparable with that from Ouriakos, a site located along the south-eastern coast of the same island, while the artefacts from Agia Marina are more problematic to interpret because they are probably to be attributed to a slightly different period. However, the most characteristic artefacts recovered from the sites are represented by microlithic geometrics obtained by abrupt, bipolar, or direct retouch, end scrapers, and different types of exhausted cores and technical pieces, which help us reconstruct the operational sequence employed for the manufacture of the armatures. The aim of the paper is to contribute to the interpretation of the characteristics of the Late Epipalaeolithic assemblages discovered on the island and to frame them into the general picture of the end of the Pleistocene in this part of the Aegean. The artefacts from the sites show unique characteristics, without parallels to the knapped stone assemblages of the same period so far recovered along the coasts of the Aegean Sea, the eastern Mediterranean, the Levant, and the Black Sea.